Newcastle disease virus: a journey from poultry to cancer - Yusoff, Khatijah (Universiti Putra Malaysia Press, 2008)

(untitled)
Infectious diseases have had a great impact on human lives and civilizations since time immemorial. Success in controlling and eradicating these diseases, on the other hand, has not only overcome human misery but expedited human progress, both individually and collectively. The eradication of smallpox and the successful control of poliomyelitis and hepatitis B can even be measured in terms of the improvement in the world’s GDP. However, new and re-emerging infections, including those connected to livestock such as the Nipah virus, SARS and avian influenza, remind us to be ever vigilant and responsive to new threats. The Newcastle disease virus (NDV) causes a highly contagious and fatal respiratory disease in chickens and other types of birds and affects the poultry industry worldwide. Although this virus is effectively controlled by vaccination, it is still endemic in Malaysia and outbreaks of the disease have contributed to major losses for the poultry industry in the country in terms of mortality and loss in egg and meat production. By delineating the genome of this enveloped negative single-stranded RNA virus, various genes have been sequenced, cloned and expressed in plasmid vectors in various organisms. Knowledge of the structural and biological characterization of NDV has provided insights into various applications of this virus in the prevention and treatment of NDV and other diseases as well. Although the virus replicates poorly in normal human cells, causing mild respiratory disease and conjunctivitis, it replicates very well in human cancer cells. This provides a potential for its use in oncology. Cancer is an omnipresent threat to human lives, especially with, but not limited to, ageing, a worldwide modern phenomenon. Its control and eradication remain largely elusive, requiring considerable concerted efforts from everyone. The oncolytic activities of the virus against human malignancies lead to tumor apoptosis and cell death. In this respect, work is in progress to leverage NDV as a viral vector to express and deliver foreign genes for vaccination and gene therapy purposes for specific malignancies in humans. This of course opens up a whole new vista in research and industry, stretching imaginations and human potentials farther, with the cherished hope of improving the lives of human beings further.